The Dissolution Characteristics of Chrysocolla in NH3-(NH4)2 CO3 Solutions. - Mena, Manolo G.
Chrysocolla samples were leached in ammonia-ammonium carbonate solutions of 0.25 to 6.00 M concentration total ammonia at a temperature range of 25 degrees to 55 degree celcius. The leaching curves for the fraction extracted, x, as a function of time follow the expression : x = loge (BS t + 1)/B which is the integrated form of the exponential rate law, assuming a linear dependence of the free energy of activation with the fraction extracted. The initial kinetics follow the Langmuir-Hinshelwood relation : rate = a (NH4+)/(1 + b (NH4+)) which is indicative of and adsorption process preceding chemical reaction.